Poligami dalam Perspektif Filsafat Hukum Islam: Studi Kasus di Desa Wonoasih, Kecamatan Wonoasih, Kota Probolinggo - Anam, Rifqi Khairul (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Polygamy, a reality embedded in the teachings of the Koran, teaches that its implementation should not be done carelessly. Not just following lust, health considerations and material capacity, but more than that, polygamy must be accompanied by the intention to seek happiness in this world and the hereafter according to Islamic law. In certain contexts, polygamy can be an effective solution to resolve challenges in family life. However, its implementation must take into account various factors according to the situation and conditions of the individual who wishes to carry it out. Polygamy laws vary according to circumstances, emphasizing the need for fairness at every step. Research regarding Islamic legal philosophy in concrete situations of polygamy needs to be carried out. The results of this research describe the understanding of partners in Wonoasih Village, Wonoasih District, Probolinggo City regarding the principles of justice in polygamous marriages according to Islamic legal philosophy. This is a positive step in strengthening the basis of public understanding of the philosophical principles of Islamic law in the realm of polygamous marriages.